A preliminary result of occupational safety and health management system compliance among gas contractor (Petroleum Pipeline) in Peninsular Malaysia - Ramat, Hamdan; Mohd Tamrin, Shamsul Bahri; Baharuddin, Mohd Rafee; Ahmad @ Ayob, Mansor (Excellent Publishers, 2014)
Occupational Safety and Health Management System (OSHMS) is a framework that provides direction for compliance with the Occupational Safety and Health (OSH) requirements pursuant to national law & regulation. In Malaysia, gas contractors that intended to register with Department of Occupational Safety and Health (DOSH) have to provide their safety manual upon registration of their company. The aim of the study is to evaluate the current status of compliance and it Critical Success Factor (CSF) as compare with Malaysia Standard MS, 1722:2011 Occupational Safety and Health (OSH) Management Systems Requirements (First Revision) among registered gas contractors in Peninsular Malaysia. A cross sectional study for nine (9) gas contractor companies using questionnaire has been done. All data consolidated in order to determine the pattern line for Occupational Safety and Health Management System current status and it Critical Success Factor (CSF) among gas contractors in Peninsular Malaysia that has registered with Department of Occupational Safety and Health. Established Questionnaire are based on Occupational Safety and Health Management System MS 1722:2011 elements requirement No 1: Policy, No 2: Organizing, No 3: Planning and Implementation, No 4: Evaluation and No 5: Action for Improvement as Parameter to come out with Descriptive Statistic for elaborating the finding and Central Tendency Measure using Mean and Standard Deviation in identifying value that deviate from standard score from elements requirement. Descriptive statistic showed that the main element score for Policy mean 74.78 and it standard deviation is 9.846, Organizing mean 74.22 and it standard deviation is 11.94, Planning and Implementation mean 80.22 and it standard deviation is 11.94, Evaluation mean 69.33% and it standard deviation 26.8 and Action for improvement mean 48.89 and it standard deviation 31.81.